Insights into clonal haematopoiesis from 8,342 mosaic chromosomal alterations. - Loh, Po-Ru; Genovese, Giulio; Handsaker, Robert E; Finucane, Hilary K; Reshef, Yakir A; Palamara, Pier Francesco; Birmann, Brenda M; Talkowski, Michael E; Bakhoum, Samuel F; McCarroll, Steven A; Price, Alkes L (Nature, 2018)
The selective pressures that shape clonal evolution in healthy individuals are largely unknown. Here we investigate 8,342 mosaic chromosomal alterations, from 50 kb to 249 Mb long, that we uncovered in blood-derived DNA from 151,202 UK Biobank participants using phase-based computational techniques (estimated false discovery rate, 6-9%). We found six loci at which inherited variants associated strongly with the acquisition of deletions or loss of heterozygosity in cis. At three such loci (MPL, TM2D3-TARSL2, and FRA10B), we identified a likely causal variant that acted with high penetrance (5-50%). Inherited alleles at one locus appeared to affect the probability of somatic mutation, and at three other loci to be objects of positive or negative clonal selection. Several specific mosaic chromosomal alterations were strongly associated with future haematological malignancies. Our results reveal a multitude of paths towards clonal expansions with a wide range of effects on human health.
Keywords: Adult; Aged; Alleles; Biological Specimen Banks; Chromosome Aberrations; Chromosome Breakage; Chromosome Fragile Sites; Chromosomes, Human, Pair 10; Clone Cells; Female; Health; Hematologic Neoplasms; Hematopoiesis; Humans; Male; Middle Aged; Mosaicism; Penetrance; United Kingdom

Phenotype diversity in type 1 Gaucher disease: discovering the genetic basis of Gaucher disease/hematologic malignancy phenotype by individual genome analysis. - Lo, Sarah M; Choi, Murim; Liu, Jun; Jain, Dhanpat; Boot, Rolf G; Kallemeijn, Wouter W; Aerts, Johannes M F G; Pashankar, Farzana; Kupfer, Gary M; Mane, Shrikant; Lifton, Richard P; Mistry, Pramod K (Blood, 2012)
Gaucher disease (GD), an inherited macrophage glycosphingolipidosis, manifests with an extraordinary variety of phenotypes that show imperfect correlation with mutations in the GBA gene. In addition to the classic manifestations, patients suffer from increased susceptibility to hematologic and nonhematologic malignancies. The mechanism(s) underlying malignancy in GD is not known, but is postulated to be secondary to macrophage dysfunction and immune dysregulation arising from lysosomal accumulation of glucocerebroside. However, there is weak correlation between GD/cancer phenotype and the systemic burden of glucocerebroside-laden macrophages. Therefore, we hypothesized that genetic modifier(s) may underlie the GD/cancer phenotype. In the present study, the genetic basis of GD/T-cell acute lymphoblastic lymphoma in 2 affected siblings was deciphered through genomic analysis. GBA gene sequencing revealed homozygosity for a novel mutation, D137N. Whole-exome capture and massively parallel sequencing combined with homozygosity mapping identified a homozygous novel mutation in the MSH6 gene that leads to constitutional mismatch repair deficiency syndrome and increased cancer risk. Enzyme studies demonstrated that the D137N mutation in GBA is a pathogenic mutation, and immunohistochemistry confirmed the absence of the MSH6 protein. Therefore, precise phenotype annotation followed by individual genome analysis has the potential to identify genetic modifiers of GD, facilitate personalized management, and provide novel insights into disease pathophysiology.
Keywords: Adult; beta-Glucosidase; Child; Child, Preschool; Female; Gaucher Disease; Genome, Human; Hematologic Neoplasms; Humans; Individuality; Male; Pedigree; Phenotype; Sequence Analysis, DNA; Siblings